2008
DOI: 10.1111/j.1365-2834.2008.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotional intelligent leadership on staff nurse empowerment: the moderating effect of span of control

Abstract: Every effort must be made to ensure that managers have reasonable spans of control that allow them to develop and use the leadership skill necessary for empowering their staff to practice to the full scope of their professional role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 40 publications
5
109
2
3
Order By: Relevance
“…This result goes in the same line with Burns who reported that, responsibility held at hand is considered as an important motivator which ties directly to sense of leadership self-efficacy [26]. The current result is consistent with Lucas et al who found that, front-line nurse mangers rated themselves highly efficacious [26].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result goes in the same line with Burns who reported that, responsibility held at hand is considered as an important motivator which ties directly to sense of leadership self-efficacy [26]. The current result is consistent with Lucas et al who found that, front-line nurse mangers rated themselves highly efficacious [26].…”
Section: Discussionsupporting
confidence: 82%
“…The current result is consistent with Lucas et al who found that, front-line nurse mangers rated themselves highly efficacious [26]. Also, McCormick and Tanguma reported high mean score for overall leadership selfefficacy score [23].…”
Section: Discussionsupporting
confidence: 82%
“…Although demonstrating weak claims for causality it is suggested that work-place organisational structures are foundational in shaping and enhancing work experience and employee work life (p970), furthermore it was found that highly emotionally intelligent nurse leaders may not be able to have a positive impact on staff empowerment if their span of control is too wide and prevents them interacting directly with their staff. [46] This demonstrates that although emotionally intelligent leadership is central to effective staff support, it can be undermined by the organisational structure. Even if the leader demonstrates emotionally intelligent leadership, it will have limited impact if the structure prevents the leader Published by Sciedu Press engaging frequently and directly with staff.…”
Section: Leadership and Staff Supportmentioning
confidence: 99%
“…[43] It was concluded that emotionally intelligent leadership skills are vital in order to create a supportive environment and facilitate positive empowerment processes leading to staff well-being. [44] In an empirical study designed to explore the relationship of emotionally intelligent leadership to nurse empowerment Lucas et al [46] conducted a predictive non-experimental survey involving 203 acute care nurses from two hospitals in Canada. EI in this context was defined as an individual's ability to manage themselves and their relationships effectively.…”
Section: Leadership and Staff Supportmentioning
confidence: 99%
“…2 Effective nurse leaders are described as possessing knowledge and skills in emotional intelligence, particularly insight and empathy, good communication, and giving and receiving feedback. 3,4 Other beneficial leadership attributes include the ability to act as an inspirational role model and to employ clarity. 6,7 The literature highlights the components of effective person-centered leadership as an approach to leading, where there is an ability to choose the right style in the right situation, and is described as achieving balance between transactional and transformational leadership styles.…”
Section: Introductionmentioning
confidence: 99%